Resolving the paradox of choice by leveraging the long tail of micro-communities – the case of the mass customising company Spreadshirt.com. (16th November 2010) - Enders, Albrecht
In recent years, many companies have implemented mass customisation approaches to differentiate themselves from competitors. The literature has highlighted the benefits of this approach which result primarily from the ability to fulfil idiosyncratic customer preferences regarding specific product specifications. Researchers have also pointed out important drawbacks and here, most importantly, the danger of mass confusion. However, research concerning the possibilities of addressing the trade-off between broad choice and high complexity is still limited. Building on the insights of the long tail framework, I argue that the democratisation of distribution is one promising possibility to overcome this trade-off. I use the case example of Spreadshirt, a mass customisation company, to illustrate this proposition.